RANCANG BANGUN SISTEM INFORMASI PENERIMAAN SISWA BARU SECARA DARING PADA MAN 02 BEKASI - Miwan Kurniawan Hidayat; Fachrudin Amin (LPPM Universitas Bina Sarana Informatika, 2016)
The rapid development of information technology accompanied by its use in a variety of fieldsincluding the field of education, in teaching and learning as well as in the operation of dataprocessing. Benefits of the use of information systems in the field of education for the delivery ofinformation and new student registration online.The problems found in this study is how a new student at MAN 02 Bekasi can be done onlinevia the Internet so that the delivery of information and new students can be more efficiently byquickly and accurately which will support the performance of the organization.The conclusion of the study is to be designed and built information system admission of newstudents online, then the admissions process from registration to reporting information can becarried out more easily, so that prospective students and management MAN 02 Bekasi can obtaininformation quickly and precisely who will support the performance, especially in the newadmissions process.Keywords: System Information, Registration, Registration Information System.